High-performance removal of toxic phenol by single-walled and multi-walled carbon nanotubes: Kinetics, adsorption, mechanism and optimization studies - Dehghani, Mohammad Hadi; Mostofi, Masoome; Alimohammadi, Mahmood; McKay, Gordon; Yetilmezsoy, Kaan; Albadarin, Ahmad B.; Heibati, Behzad; AlGhouti, Mohammad; Mubarak, N. M.; Sahu, J. N. (ELSEVIER SCIENCE INC, 2016)
The adsorption capabilities of two nano-sized adsorbents: multi-walled carbon nanotubes (MWCNTs) and single-walled carbon nanotubes (SWCNTs) were investigated for the removal of toxic phenol. The maximum adsorption capacities of MWCNTs and SWCNTs were determined as 64.60 and 50.51 mg/g, respectively. Adsorption kinetics followed the pseudo-second order model for both adsorbents. The optimum conditions using SWCNT5 and MWCNTs were pH 6.57 and 4.65, phenol concentration 50 and 50 mg/L, dose 1.97 and 2 g/L and contact time 36 and 56 min, respectively. The results indicated that MWCNTs and SWCNT5 were proven as high-performance adsorbents for toxic phenol removal from wastewater. (C) 2015 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Adsorption; Carbon nanotubes; Kinetics; Optimization; Phenol; BAGASSE FLY-ASH; ACTIVATED CARBON; AQUEOUS-SOLUTIONS; WASTE-WATER; DYE; EQUILIBRIUM; THERMODYNAMICS; ISOTHERM; SORPTION; 4-NITROPHENOL; Chemistry; Engineering